Intellectual Capital: A Key Driver of Financial Performance in The Macedonian Banking Industry - Bojan Malchev; Atanasko Atanasovski; Marina Trpeska (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- How does intellectual capital, measured by the Value Added Intellectual Coefficient (VAIC) and its components, influence the financial performance of banks in North Macedonia? Motivation- In the evolving landscape of the banking sector, understanding the impact of intellectual capital on financial performance is crucial. This study builds upon existing research (Appuhami, 2007; Ozkan et al., 2017; Joshi et al., 2013) to explore this relationship in the specific context of North Macedonia. It addresses the research gap by using the VAIC model to quantify intellectual capital and examines its effect on Return on Assets (ROA) and Return on Equity (ROE). Idea- The research employs linear regression models to analyze the effect of intellectual capital, as measured by VAIC and its components, on the financial performance indicators ROA and ROE in Macedonian banks. Data- The study analyzes a decade of data (2012-2021) from ten Macedonian banks, using the VAIC model to measure intellectual capital. Tools- The study utilizes linear regression analyses with the Statistical Package for the Social Sciences (SPSS) to examine the relationship between intellectual capital and financial performance. Findings- The study finds a significant and positive impact of VAIC and its components on both ROA and ROE. These results underscore the importance of intellectual capital in enhancing financial performance in the banking sector. Notably, the study reveals a high average VAIC value among Macedonian banks, indicating their substantial intellectual capability. Contribution- This research adds to the literature by elucidating the relationship between intellectual capital, measured through VAIC, and financial performance in the banking sector of North Macedonia.
Keywords: G21; O34; M41; 650; Intellectual capital; Financial performance; North Macedonia; Value Added Intellectual Coefficient (VAIC); Banking sector